If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2x + -3) = 12 + -4x Reorder the terms: 4(-3 + 2x) = 12 + -4x (-3 * 4 + 2x * 4) = 12 + -4x (-12 + 8x) = 12 + -4x Solving -12 + 8x = 12 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -12 + 8x + 4x = 12 + -4x + 4x Combine like terms: 8x + 4x = 12x -12 + 12x = 12 + -4x + 4x Combine like terms: -4x + 4x = 0 -12 + 12x = 12 + 0 -12 + 12x = 12 Add '12' to each side of the equation. -12 + 12 + 12x = 12 + 12 Combine like terms: -12 + 12 = 0 0 + 12x = 12 + 12 12x = 12 + 12 Combine like terms: 12 + 12 = 24 12x = 24 Divide each side by '12'. x = 2 Simplifying x = 2
| 49-6x=13+12x | | x^2+16x=16 | | 34-9x=15+10x | | 60+60*0+1=f | | 4/12+6/12+8/12 | | 13x^2-7x+3=0 | | -8+8(6-4M)= | | 6-9x=7-9x+20 | | -8=8(6-4) | | log(1/5)x | | 0=x^2-13x+36 | | 1/4x+5=1/3x | | 8x+5x-40=60-7x | | (5/3x-2)=(2/x+1) | | 5/3x-2=2/x+1 | | 4x/x^2-16=(16/x^2-16)-(4/x+4) | | 49=3(1+2x)+4 | | x^2+3x+2x+6=x^2-10 | | x/x-5+8=5/x-5 | | (x/x-5)+8=5/x-5 | | z(z^3+1)=2+z^4 | | 28x+21=42x-14 | | x(2x-2)=(2x+7)(x-1) | | 28x+21=42x+14 | | 175m-125m+43200=45450-175m | | (-2x+4)(5x-6)= | | (3m^-3/2n^-2)^-3 | | 6x^3-33x^2+45x=0 | | (7-2)p=5-8 | | 1/3g+4=2 | | 2/7p+8=1/2p+5 | | 23=9+7x |